The impact of cybersecurity law in the middle east - Srbaz Nidham Othman; Aqeel Mahmood Jawad; Raed Hameed; Raad Tomaa Kawad; Dmytro Khlaponin (Encuentros)
Due to the growing digitalization in the Middle East, there has been a significant increase in cyberattacks in the region. The escalating magnitude of cyber assaults underscores the urgent need for robust cybersecurity measures and regulatory frameworks to safeguard digital assets and infrastructures. The articles aim to assess the repercussions of cybersecurity legislation in the Middle East, with a focus on the challenges and accomplishments of the region in establishing effective cybersecurity defenses. A comprehensive analysis of scholarly articles, media reports, and government records was conducted to gather comprehensive data on the existing cybersecurity rules in the Middle East. This method facilitated a thorough analysis of the legal and regulatory structure in the given domain. Analysis reveals that while certain Middle Eastern countries have made significant progress in establishing comprehensive cybersecurity frameworks, there are still significant areas for improvement that hinder the practical application of these frameworks. A significant revelation is the need for cohesive efforts and cooperation among governments, business sector entities, and international agencies, which is vital for enhancing cybersecurity.